General Confiscation on Bankcrupty and Confiscation on Criminal Verdict: Sita Umum berdasarkan Kepailitan dan Sita berdasarkan Putusan pidana - Putri, Victoria Pasari (Universitas Muhammadiyah Sidoarjo, 2020)
General confiscation of bankruptcy and criminal confiscation often occur simultaneously, this has led to debate on both sides between the prosecutor and the curator. Prerihal who is most entitled to the property of palilit and confiscated goods into a long discussion. However, if explained clearly, it will be found that public confiscation can precede criminal confiscation. In this journal, the author tries to discuss the substance and outline of the forgery by using normative writing procedures and applicable statutory regulations. In terms of the benefits of the debt and debt problem can be resolved as soon as possible and as fair as possible so that the economy is disrupted, both economies of a small scale and economies of large scale by continuing to pay attention to the Principle of Proportionality which consumes rights and obligations so that everything is in context and achieves goals that are expected to be fair to every one. In terms of legal certainty, Article 31 of the KPKPU Law that mentions all confiscations, appointed when the debtor's bankruptcy is pronounced is a new regulation and a special regulation compared to the confiscation of criminal provisions contained inArticle 39 paragraph (2) of the Criminal Procedure Code.